MASS, MORPHOLOGY, AND GROWTH RATES OF MOOSE IN NORTH DAKOTA - Jensen, William F.; Smith, Jason R.; Maskey Jr., James J.; McKenzie (Deceased), James V.; Johnson (Retired), Roger E. (Lakehead University, 2013)
This paper provides predictive formulas to estimate live weights of moose (Alces alces andersoni) from hunter-harvested animals and evaluate growth rates of moose in North Dakota, and reviews weight-related measurements among moose populations. From 1978–1990, morphometric data were collected on 224 hunter-killed moose harvested after the rut (10 November–12 December) in North Dakota. Body mass increased rapidly for both sexes from 0.5 years to 1.5 years-of-age. Whole weight and total body length reached an asymptote for both sexes by 5.5 years; mean whole weight appeared to decline among older individuals. Although field dressed weight was the best predictor of whole weight (r2 = 0.93; n = 154), total body length provided reasonably good estimates of whole weight (r2 = 0.76; n = 153). Whole weight estimates based upon shoulder height (r2 = 0.33; n = 158) and hind-foot length (r2 = 0.46; n = 163) were less reliable. We also used morphometric variables to predict field dressed weight, carcass weight, and visceral weight. Field dressed weight was the best predictor of antler width (r2 = 0.72; n = 108) and antler width was a good predictor of male age (r2 = 0.70; n = 119). When compared to other North American populations, average weights of moose harvested in North Dakota tended to be higher in all age classes. Additionally, the calf-to-yearling growth rate of female moose in North Dakota was as high, or higher than in other populations. Morphometric comparisons of free-ranging moose from various North American populations had much size overlap, with southern and eastern moose populations tending to have largest average adult body mass. Sexual dimorphism of mature North Dakota moose (> 4.5 years) was comparable to that in other populations.